Inherited and Environmental Factors Influence Human Monocyte Heterogeneity - Patel, Amit A.; Yona, Simon (Frontiers in Immunology, 2019)
Monocytes originate in the bone marrow before being released into the circulation. Circulating monocytes are composed of multiple subsets, each with specialised functions and are recruited to repopulate resident monocyte-derived cells in the periphery or to sites of injury. A number of extrinsic factors influence the function and quantity of monocytes in the blood. Here we outline the impact of sex, ethnicity, age, sleep, diet and exercise on monocyte subsets and their function, highlighting steady state is not a single physiological condition. A firm understanding of the interplay of these factors with the immune system may allow for better targeted therapy in the future.